Monetary policy in Turkiye during economic turbulence (2016-2023) : the impacts of COVID-19 and post-pandemic recovery - Kardes, Nil Deniz (2025)
This thesis examines the effectiveness and resilience of the monetary policy of Türkiye in the period 2016-2023, specifically that of the Central Bank of the Republic of Türkiye (CBRT) before and after the COVID-19 pandemic. The hypothesis posits that the CBRT’s monetary policy adjustments during COVID-19, while stimulating short-term economic growth, contributed to persistent inflation and currency instability, posing challenges to long-term economic stability and recovery in Türkiye Employing a time-series econometric methodology that makes use of Vector Autoregression (VAR), Vector Error Correction Model (VECM), and Ordinary Least Squares (OLS) with dummies for structural break, this research examines dynamic relationships between most important macroeconomic variables like inflation, exchange rate, interest rate, money supply, industrial output, and joblessness. The results provide considerable short-run inflationary effects of depreciation and monetary expansion with very little long-run adjustment, in direction suggestive of high-powered persistent inflation and bad policy credibility. The post-COVID period suggests a structural break in inflation behavior, in direction indicative of a shift from pre-pandemic monetary behavior. Also, the Granger causality tests provide a feedback relation between inflation and exchange rate while interest rates appear to be quite inefficient in explaining unemployment. Under the Taylor Rule and time inconsistency theory, the thesis contends that the monetary policy of Türkiye had lacked systematic discipline to ensure price stability and proposes moving towards a rule-based system underpinned by fiscal harmonization and institutional change. The research adds to the body of knowledge on monetary policy challenges in the emerging markets and offers evidence-based policy recommendations for improving macroeconomic stability.